Conventional and In Vitro Propagation of Lechenaultia macrantha (Goodeniaceae) - Png, G.; Downes, Katherine; Tan, B. (American Society for Horticultural Science, 2012)
Lechenaultia macrantha K. Krause (Goodeniaceae) is a species with great horticultural potential that is endemic to the sandy and gravelly soils of central, southwestern Australia. The effectiveness of several conventional and in vitro propagation techniques were assessed. Seeds possessed non-deep physiological dormancy, and a combination of seed nicking and imbibition in 10% (v/v) smoke water for 24 hours resulted in 81% germination after 33 days of incubation. Softwood stem cuttings produced adventitious roots readily without the need for exogenous auxin application. In vitro microcuttings produced shoots in response to cytokinins. However, optimal or suboptimal cytokinin concentrations resulted in hyperhydric shoots, which poses an obstacle to successful micropropagation. The use of auxin was necessary for the initiation of adventitious roots in vitro. This information will assist in the horticultural development of this species.